Relationship Between Tumor Necrosis Factor-α rs361525 Polymorphism and Gastric Cancer Risk: A Meta-Analysis - Xu, Tianshu; Kong, Zhijun; Zhao, Hui (Frontiers in Physiology, 2018)
Tumor necrosis factor alpha (TNF-α) is an important molecule in inflammatory, infectious and tumor processes, which plays a crucial role in the early stages of gastric cancer (GC). TNF-α rs361525 polymorphism has been demonstrated to be associated with GC risk; however, the association remains conflict and controversial. We therefore conducted this meta-analysis to obtain a more precise estimate of the association of TNF-α rs361525 polymorphism with GC risk. A comprehensive database search of PubMed, Web of Science, EMBASE, and CNKI databases was performed to identify relevant studies through October 5, 2017. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association. A total of 20 studies were included in this meta-analysis involving 4,084 cases and 7,010 controls. There was no significant association between TNF-α rs361525 polymorphism and GC risk in the overall populations. In the subgroup analysis, we found that TNF-α rs361525 polymorphism was associated with the increased risk of GC among Asians, while rs361525 polymorphism decreased the risk of GC among Caucasians. Subgroup analysis by genotyping methods revealed increased risk for other methods. In conclusion, this meta-analysis shows that TNF-α rs361525 polymorphism is associated with the risk of GC.